2012
DOI: 10.1124/jpet.111.190116
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drug-Activated Gene-1 Plays a Role in the Impairing Effects of Cyclooxygenase Inhibitors on Gastric Ulcer Healing

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) can impair gastric ulcer healing. This study investigates the involvement of NSAIDactivated gene-1 (NAG-1) in ulcer repair impairment by cyclooxygenase (COX) inhibitors. Gastric ulcers were induced in rats by acetic acid. Four days later, animals received daily intragastric indomethacin (nonselective COX-1/COX-2 inhibitor; 1 mg/kg), 5-(4-chlorophenyl)-1-(4-methoxyphenyl)-3-trifluoromethylpyrazole (SC-560) (selective COX-1 inhibitor; 2.5 mg/kg), (5-dimethyl-3-(3-flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The gastric lesion indexing was performed as described by several works [ 38 41 ]. In brief, a dissecting microscope of the lesion area (mm 2 ) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…The gastric lesion indexing was performed as described by several works [ 38 41 ]. In brief, a dissecting microscope of the lesion area (mm 2 ) was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Retarded epithelial cell restitution Though the precise net outcome of NSAID action on cell proliferation remains unclear, NSAIDs and responsible gene, NSAID-activated gene-1 either confer inferior mucosal integrity or delay the epithelial restitution [17].…”
Section: Classical Mechanisms Of Nsaid-induced Gastroduodenal Damagesmentioning
confidence: 99%
“…Although NAG-1 is involved in acute stress-induced apoptotic process (10), increasing recent evidences demonstrated that NAG-1 can trigger homeostatic cellular responses and play protective roles in both physiological and pathological states, including chronic inflammation and tumorigenesis (16)(17)(18)(19). In response to the cytotoxic NSAIDs, cells also can produce the survival signals.…”
Section: Discussionmentioning
confidence: 99%
“…Although most intestinal epithelial cells maintain a low level of NAG-1 expression, apoptotic mucosal surface epithelial cells can have relatively high levels of NAG-1 (15). Although NAG-1 is involved in acute stress-induced apoptotic process (10), increasing recent evidences demonstrated that NAG-1 can trigger homeostatic cellular responses and play protective roles in both physiological and pathological states, including chronic inflammation and tumorigenesis (16)(17)(18)(19). NAG-1, one of the major secreted proteins induced by p53, is thought to be important for promoting p53-mediated activity associated with cell cycle arrest and apoptosis (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation